The lost & found - Leno, Katrina (HarperTeen, an imprint of HarperCollinsPublishers, 2016)
"Fannie and Louis both belong to an online support group for trauma survivors. They both also have a strange tendency to lose things. But when they embark on a road trip to finally meet each other, they stat to realize that the things you lose might be things you weren't meant to have at all, and that you never know what you might find if you just take a chance"...
Keywords: JUVENILE FICTION / Social Issues / Emotions & Feelings; JUVENILE FICTION / Family / Siblings; JUVENILE FICTION / Social Issues / Friendship; Loss (Psychology); Post-traumatic stress disorder; Friendship; Brothers and sisters; Families; Automobile driving; Jugendbuch